(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
the research was exposed to a study the importance of the role of the supportive entities in providing the useful information to the tax administration and their ability to extend the level of the tax base of taxpayers, through the improvement of the tax payers determination and their tax settle for the purpose of increasing the tax revenue, and shed light on the legal evidence through which these entities become officially assigned to perform a supplementary task to the General Committee for Taxes GCT, to help it to perform its task efficiently, and to study the reasons of the weak cooperation of the supportive entities and their reluctance to provide useful information which leads to limiting the tax base. The research data have been collected from some supportive entities to the tax work of the health sector through the statistics of their registered taxpayers as well as, the statistics of the taxpayers that are registered at the GCT to observe the difference between those statistics. The research is based on a primary hypothesis that suggests that there is a strong relationship between the effectiveness of the role of the supportive entities and the expansion in the determination of the tax bases of the taxpayers, and in turn, increasing the collected tax revenue. In general, the results indicated that there is a weakness in the response of the supportive entities of the tax work and consequently weak cooperation with GCT. This matter has negatively reflected on the process of obtaining information that contributes in determining the tax base of the taxpayers and a reduction in tax revenue.